On rules - Colombo, Gherardo (Amsterdam University Press, 2015)
Justice is simultaneously a practical and an ideal concept: when we think of justice, we refer to its day-to-day administration, involving police, lawyers, judges, and politicians-but we also refer to a larger ideal, a set of basic values that guide our attempts to live together and balance competing interests, obligations, and freedoms. If we lose sight of the practical, the ideal will fail-but if we forget the ideal, the practical becomes pointless. On Rules is the culmination of decades of thinking about and working within the law as both ideal and realm of practical action. Gherardo Colombo brings to his rich philosophical analysis of the culture of justice thirty years of experience in the Italian judiciary, which saw him head up numerous important and sensitive commissions and inquiries. His exploration of the concept and application of rules of justice is powerful and clear: if we don't root our experience in a fundamental respect for rules, we cannot have a functioning, just society.